2008
DOI: 10.1093/jac/dkn420
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pegylated interferon plus ribavirin treatment in HIV/hepatitis C virus co-infected patients receiving abacavir plus lamivudine or tenofovir plus either lamivudine or emtricitabine as nucleoside analogue backbone

Abstract: HIV-infected patients who receive abacavir plus lamivudine respond worse to pegylated interferon plus ribavirin than those who are given tenofovir plus lamivudine or emtricitabine as N(t)RTI backbone, especially in those receiving lower ribavirin doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 22 publications
0
37
2
3
Order By: Relevance
“…81,85 Some controversy exists as to whether concomitant abacavir may be associated with a reduced response to pegylated interferon and ribavirin, [86][87][88] but a recent in vitro study showed that the anti-HCV activity of ribavirin was not modified by abacavir. 89 It is important to achieve adequate ribavirin trough levels via weight-based dosing, 85,90 and there is insufficient evidence to recommend avoiding this combination.…”
Section: Hepatitis Cmentioning
confidence: 99%
“…81,85 Some controversy exists as to whether concomitant abacavir may be associated with a reduced response to pegylated interferon and ribavirin, [86][87][88] but a recent in vitro study showed that the anti-HCV activity of ribavirin was not modified by abacavir. 89 It is important to achieve adequate ribavirin trough levels via weight-based dosing, 85,90 and there is insufficient evidence to recommend avoiding this combination.…”
Section: Hepatitis Cmentioning
confidence: 99%
“…Consider liver biopsy particularly for those with genotype 1 or 4 infection where the results of HCV therapy remain Table 3 Interactions between antiretroviral agents and anti-hepatitis C virus (HCV) therapy [186][187][188][189][190][191][192]239] [198,200,201]. The risk-benefit of liver biopsy should be considered in the individual patient.…”
Section: General Principles Of Anti-hcv Therapymentioning
confidence: 99%
“…HCV ve HIV ile ikili infeksiyonu olan olgularda PegIFN kullanımına bağlı olarak gelişebilecek nötropeni ve trombositopeni, KHC tedavisindekinden farklı değildir. PegIFN dozunun azaltılmasıyla bu durum önlenebilir (169)(170)(171)(172)(173)(174)(175)(176)(177)(178)(179)(180).…”
Section: Hcv Hbv Ve Hiv Koinfeksiyonunda Tedaviunclassified